PROBLEM-SOLVING IN EDUCATION: TEACHING STUDENTS TO THINK LIKE INNOVATORS - Yomg’irova Durdona Begzod qizi; Komiljonova Mavluda Abduvaliyevna (TADQIQOTLAR.UZ, 2024)
Problem-solving is a critical skill that empowers students to face challenges, make informed decisions, and adapt to the complexities of the modern world. Teaching students to think like innovators involves fostering creativity, critical thinking, and adaptability—skills essential for academic success, personal growth, and future career readiness. This article explores the significance of problem-solving in education and examines  strategies  educators  can  employ  to  nurture  innovative  thinking  among students. Key strategies include implementing inquiry-based learning, teaching design thinking, promoting collaborative group work, and incorporating real-world challenges into  the  learning  process.  Furthermore,  the  article  emphasizes  the  importance  of cultivating a growth mindset and integrating technology as a tool for creative problem-solving. Through these strategies, educators can prepare students to not only solve problems but also approach them with innovative and flexible solutions. This shift from traditional rote learning to innovative problem-solving paradigms equips students with the tools to navigate an increasingly complex and rapidly changing world.